Psyclub: A Psychology-Based Extracurricular To Improve Mental Health Literacy Of Rural Youth Communities Through Schools - Nadia Syarifah Mumtaz; Devina Fadzila Rochim; Myllani Tsesar Caturjuniandri (Psycho Holistic, 2021)
Community mental health is a community's ability to adapt or adapt to problems in life in a good and harmonious manner. Nowadays, people with serious mental disorders in Indonesia still experience shackling and mistreatment. Therefore an optimal strategy needs to be implemented for every individual, family and community with a comprehensive, integrated and sustainable promotive, preventive, curative and rehabilitative approach. This study used the literature review method by examining several literature sources regarding the mental health of rural communities, mental health literacy, and extracurricular activities in schools. Based on the literature review, we found the concept of mental health literacy which is very important to be improved in the community. Mental health literacy itself is defined as the ability to recognize specific disorders, know how to seek mental health information, knowledge about risk factors and causes, knowledge about self-care and seeking available professional help, and attitudes that promote recognition and seek appropriate help. In relation to this matter, we also found the potential of extracurricular activities as a means to improve mental health literacy, more specifically among rural youth who are expected to become mental health agents for their communities. Extracurricular activities are not only believed to influence adolescent behaviors, but they are also thought to have an impact on psychological well-being. Research indicates that activity participation can have two possible effects on psychological wellbeing: either as a deterrent or as a promoter of mental health. The result of this research is a program design of "Psyclub", an extracurricular activity in schools with the aim of developing student character and increasing knowledge and skills regarding mental health through the Mental Health Ambassador program; Contribute Work "Psyclub"; "Psyclub" Daily Challenge (PDC); Peer Counseling; and Lively Psychological Literacy. Suggestions for further research are the improvement of the "Psyclub" program as well as further and in-depth research related to the needs needed by the community, especially junior and senior high school students.